THERMOGRAVIMETRIC STUDY OF PHASE TRANSFORMATIONS OF METAL OXIDE COMPOSITES BASED ON HIGHLY DISPERSIVE INERT CARRIERS IN THE SYNTHESIS OF CO2 METHANATION CATALYSTS: DOI: https://doi.org/10.17721/1728-2209.2023.1(58).7 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. Previously synthesized nanoparticles of nickel and cobalt oxide based on fumed silica have proven themselves as promising catalysts for CO2 methanation reaction. Although TiO2 nanoparticles are widely used as a catalyst carrier for nanoparticles of both noble metals and other metal oxides, but pure oxides always have some disadvantages as starting materials for further synthesis of catalysts. In addition, there is no reliable information about catalysts based on transition metals (Ni, Co, Fe) deposited on highly dispersed mixed nanooxides with detailed studies of their surface composition. Therefore, the aim of this work was to study the influence of carriers such as alumina-silica and alumina-titanium-silica on thermal transformations of grafted metal oxide (Ni-Fe and Co-Fe) composites during the synthesis of CO2 hydrogenation catalysts.Methods. In this work, the process of restoring NiFe and CoFe catalysts based on mixed pyrogenic oxide carriers to their metallic state was investigated using thermogravimetric analysis (TGA).Results. It was established that the formation of applied metal oxide composites by the reduction of metal oxide precursors is determined by the nature of the metals and depends on the used carrier. It was determined that the process of reduction of the NiFe-oxide precursor begins at a temperature of 200–250 °C and is characterized by activation energy values of about 76–86 kJ/mol. The activation energies of the reduction of the CoFe-oxide precursor are higher and amount to 91–95 kJ/mol, which leads to an increase in the reduction temperatures by 50–100 °С.Conclusions. The use of alumino-silica brand SA96 as a carrier leads to a decrease in activation energy and reduction temperatures, compared to the carrier brand AST1 (alumino-titanium-silica), which is explained by the smaller specific surface area of SA96 and the greater availability of the oxide precursor for reduction.
Keywords: supported catalysts, CO2 methanation, thermogravimetric analysis, pyrogenic carriers, metal oxide precursors.